Pengaruh Kualitas Produk, Brand Image, dan Promosi Terhadap Keputusan Pembelian Produk Nivea di Kota Batam (Jurnal Riset Rumpun Ilmu Ekonomi, 2026)
This study aims to analyze the influence of product quality, brand image, and promotion on purchasing decisions for Nivea products in Batam City. The population in this study were consumers who use Nivea products in the Lubuk Baja District area with an unknown population size. The sampling technique used the Jacob Cohen formula, resulting in a sample size of 204 respondents using a purposive sampling method. The research data were analyzed using multiple linear regression methods supported by data quality testing, classical assumption tests, influence tests, and hypothesis tests. The results of the regression analysis showed that product quality had a 31.5% influence on purchasing decisions, brand image had a 62.7% influence, and promotion had a 27.4% influence on purchasing decisions. Furthermore, the results of the coefficient of determination test showed that the variables of product quality, brand image, and promotion were able to explain 83.2% of the variation in purchasing decisions. In addition, the results of the T test and F test proved that the three independent variables had a positive and significant influence, both partially and simultaneously, on purchasing decisions for Nivea products in Batam City.